Cardio-metabolic risk stratification and life style interventions for risk reduction among overweight and obese school children - Shardul Kamale; Ipseeta Ray Mohanty; Vijay Kamale; Nimain Mohanty; Sabita Dash Mishra (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2020)
Background and Objectives: Childhood obesity strongly correlates with risk of developing type 2 diabetes and cardiovascular disease in the future. Screening of school children for diabetes and cardiovascular disease risk will be effective in identifying children at risk of developing cardio metabolic diseases and successfully enrolling them in a lifestyle modification program.  Methodology: School children in the age group of 10-18 years were screened using BMI as a determining tool for obesity. The Healthy Heart Score for CVD risk prediction and Indian Diabetes Risk Score (IDRS) were used to categorize the obese and overweight children as having high, medium and low CVD and diabetes risk. The participants were imparted educational intervention based on WHO CVD Risk Reduction Guidelines and the impact of structured educational intervention was assessed.  Results: In the present study, out of the 305 children who were screened, 10.16% were found to be overweight and 3.93% were obese. Maximum proportion of overweight children fell under the moderate risk of developing diabetes (68.2%) category whereas proportion of obese children with moderate and high diabetes risk was found to be 44.4% and 55.5% respectively. In addition, it was observed that 31.2% of overweight children had moderate CVD risk and 68.2% had high CVD risk. Among the obese children, 11.1% were stratified as having moderate CVD risk and 88.9% as high CVD risk.  Structured educational intervention resulted in a significant increase in knowledge regarding preventive Strategies for Cardio-metabolic risk modification.  Conclusion: 74.2% and 35.5% of obese and overweight children were stratified as having high CVD risk and diabetes risk respectively. Educational Intervention resulted in a significant increase in knowledge regarding preventive strategies for CVD and Diabetes Risk {related to weight control, salt intake, saturated fat restriction, physical activity, maintaining blood pressure} among obese or overweight children.